2017
DOI: 10.1159/000480396
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Maternal Gestational Hypertension and the Use of Anti-Hypertensives on Neonatal Myocardial Performance

Abstract: Background: Assessment of myocardial performance in neonates using advanced techniques such as deformation imaging and rotational mechanics has gained considerable interest. The applicability of these techniques for elucidating abnormal myocardial performance in various clinical scenarios is becoming established. We hypothesise that term infants born to mothers with gestational hypertension (GH) may experience impaired performance of the left and right ventricles during the early neonatal period. Objectives: W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
5
1
Order By: Relevance
“…Studies of the association between maternal preeclampsia or GH and newborn cardiac structure and systolic function assessed by conventional echocardiography are limited and have had small sample sizes (maximum 80 preeclampsia-exposed children). 20 , 21 Breatnach et al 21 found left ventricular systolic dysfunction with significantly lower ejection fraction within 48 hours of birth in infants born at term to mothers with GH, compared with infants born to healthy mothers, which contrasts with our findings of larger fractional shortening in infants exposed to preeclampsia but not in infants exposed to GH. Aye et al 20 found that although left and right ventricular masses were similar at birth in infants born at term after pregnancies with preeclampsia, GH, and no HDP, respectively, right ventricular end-diastolic volume was smaller in infants exposed to HDPs, preeclampsia in particular.…”
Section: Discussioncontrasting
confidence: 97%
“…Studies of the association between maternal preeclampsia or GH and newborn cardiac structure and systolic function assessed by conventional echocardiography are limited and have had small sample sizes (maximum 80 preeclampsia-exposed children). 20 , 21 Breatnach et al 21 found left ventricular systolic dysfunction with significantly lower ejection fraction within 48 hours of birth in infants born at term to mothers with GH, compared with infants born to healthy mothers, which contrasts with our findings of larger fractional shortening in infants exposed to preeclampsia but not in infants exposed to GH. Aye et al 20 found that although left and right ventricular masses were similar at birth in infants born at term after pregnancies with preeclampsia, GH, and no HDP, respectively, right ventricular end-diastolic volume was smaller in infants exposed to HDPs, preeclampsia in particular.…”
Section: Discussioncontrasting
confidence: 97%
“…Caglar et al reported a significant enlargement of RV and RA, and deterioration of RV systolic and diastolic function in women with preeclampsia comparing with controls [ 19 ]. Some researches reported enlarged RV, increased pulmonary arterial pressure and reduced RV longitudinal strain in patients with pregnancy-induced hypertension [ 6 9 ], whereas others did not find significant difference between these patients and normotensive controls [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with acute preeclampsia RV global strain was significantly lower than in normotensive controls and this was particularly noticed for basal and apical RV segments [ 6 , 9 ]. Yu et al reported lower RV longitudinal strain in women with preeclampsia than in normotensive controls, [ 3 ], whereas other studies found no difference in RV global longitudinal strain [ 8 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence suggests that the maternal use of labetalol for pregnancy-induced hypertension may reduce LV performance at birth. The clinical implications of this phenomenon remain unstudied 42. Endocrine disorders such as adrenal haemorrhage and adrenogenital syndromes result in BP instability and can lead to a fall in both systolic and diastolic BPs.…”
Section: Clinical Scenarios Leading To Low Blood Flow Statesmentioning
confidence: 99%